PWE-171 Bone Morphogenetic Protein (BMP) Pathway Dysregulation Subverts Oncogene Induced Senescence Mechanisms in the Serrated Pathway of Tumourigenesis. (4th June 2013) - Boitsova, T; Rafferty, H; Davis, H; Bardella, C; Gill, P; East, J; Tomlinson, I; Chetty, R; Silver, A; Leedham, S
Abstract : Introduction: The serrated colorectal carcinogenesis pathway is increasingly recognised as a distinct and important route to CpG island methylated phenotype (CIMP) carcinomas, yet comparatively little is known about the molecular pathogenesis of these lesions. The precursor lesions - hyperplastic and serrated polyps, are initiated by BRAF or KRAS mutations which initially induce proliferation but are followed by activation of oncogene-induced senescence (OIS) pathways resulting in telomere independent cell-cycle arrest. Subversion of OIS mechanisms is thus necessary for progression of serrated lesions. We assessed (epi)genetic mutation burden and morphogen expression in different colorectal polyps and investigated the effect of disrupted morphogen balance on OIS systems Methods: Colonoscopic samples of hyperplastic, serrated, conventional adenomas and neighbouring normal tissue were used. Individual crypt gene expression was measured, DNA extracted and (epi)mutation burden assessed. Epigenetic silencing of the BMP antagonist GREM2 was assessed in serrated polyps and a methylated cell-line. K-rasV12 transfection of mouse embryonic fibroblasts (MEF) was used to induce OIS and assess dynamic morphogen changes in senescing cells. shRNA knockdown of BMP4 in a cancer (HCT116) and primary immortalised (HCEC) cell-line was used to reverse the changes seen in human polyps. Results: Marked BMP component changes were seen in both serrated and traditional adenomas, with fewer changes in rectal hyperplastic polyps. Only serrated polyps showed aberrant gene methylation, including epigenetic transcriptional silencing of the BMP antagonist GREM2 . Differential BMP ligand expression ( BMP2 downregulated, BMP4 upregulated) was noted in adenomas and confirmed with in situ hybridisation. KrasV12 OIS induction in MEF's caused the reversed expression pattern of BMP ligands to that seen in polyps, a change not seen in replicative senescence of the same cells. BMP4 shRNA knockdown impeded anchorage-dependent growth of HCT116 cells and provoked a rapid cell senescence response in HCEC cells with growth arrest and up-regulation of both p21 and p16. Conclusion: We hypothesise that BMP ligands are involved in mediating ( BMP2 ), or subverting ( BMP4 ) oncogene-induced senescence, and that epigenetic silencing of specific BMP pathway constituents is selected early during serrated tumourigenesis. By demonstrating the mechanistic involvement of the BMP pathway in OIS we have identified an important early tumour promoting role of morphogen dysregulation which may inform future drug development. Disclosure of Interest: None Declared.